Історична наука в УРСР як предмет дослідження в англо-американській історіографії - Лаас, Н. (Інститут історії України НАН України, 2009)
У статті відтворено образ історичної науки в УРСР у працях англо-американських учених другої половини ХХ – початку ХХІ ст. Вивчено еволюцію ролі та функцій трьох основних акторів історіографічного процесу в Радянському Союзі – влади, істориків та пересічних громадян. Визначено сталі та змінні компоненти у загальній схемі їх взаємодії. In the article the image of historical science in the Ukrainian SSR in the works of the Anglo-American researchers published during the second half of the twentieth and the beginning of the twenty-first centuries is reconstructed. The modification of roles and functions of three main actors in Soviet historiographical process – power, historians and average citizens – is examined. The invariable and change components in the general pattern of its interaction are defined.